1989
DOI: 10.1002/ar.1092230214
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic study of [3H]mannose utilization during cementoblast differentiation, formation of acellular cementuum, and development of periodontal ligament principal fibers

Abstract: The formation of acellular cementum and the deposition of [3H]mannose-labeled extracellular matrix were studied in 14-day-old Sprague-Dawley rats. The sequential events of cementogenesis and periodontal ligament formation observed by light and electron microscopy were described from the stage of an intact root sheath to postcementogenesis. Ultrastructural examination of cementoblasts and periodontal ligament fibroblasts revealed [3H]mannose labeling of the Golgi apparatus at 10 minutes, collagen secretion gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…This possibility may partially explain the relatively broader zone of NCPs observed in human teeth near the DCJ where the collagenous surface of the mantle dentin is less organized and "looser," with the collagen fibrils being more randomly organized and less dense than in rodents and where there is extensive interdigitation of cementum and dentin collagen fibrils (Bosshardt and Schroeder, 1991a,b, 1992. In species and at sites where a distinct cement line is not formed at the DCJ, then within any single tooth, variations in collagen fibril density and organization may influence the accumulation pattern of OPN and other proteins at the DCJ, an observation particularly evident in humans where there is extensive afibrillar, noncollagenous organic material among collagen fibril bundles as they branch while approaching the DCJ (Bosshardt and Schroeder, 1991a,b Bosshardt and Schroeder, 1996) and may thus correspond to this relatively collagen-free zone rich in noncollagenous glycoproteins that stain nonspecifically with ruthenium red and chromic phosphotungstic acid (Yamamoto, 1986;Yamamoto and Wakita, 1990) and labels with 3H-mannose (Cho and Garant, 1989). These and other (Kurihara and Enlow, 1980a,b) authors have discussed the possibility that noncollagenous organic material accumulating at the DCJ and at remodeling alveolar bone surfaces may serve in matrix adhesion.…”
Section: Ultrastructural Distribution and Relationships Of Matrix Promentioning
confidence: 96%
“…This possibility may partially explain the relatively broader zone of NCPs observed in human teeth near the DCJ where the collagenous surface of the mantle dentin is less organized and "looser," with the collagen fibrils being more randomly organized and less dense than in rodents and where there is extensive interdigitation of cementum and dentin collagen fibrils (Bosshardt and Schroeder, 1991a,b, 1992. In species and at sites where a distinct cement line is not formed at the DCJ, then within any single tooth, variations in collagen fibril density and organization may influence the accumulation pattern of OPN and other proteins at the DCJ, an observation particularly evident in humans where there is extensive afibrillar, noncollagenous organic material among collagen fibril bundles as they branch while approaching the DCJ (Bosshardt and Schroeder, 1991a,b Bosshardt and Schroeder, 1996) and may thus correspond to this relatively collagen-free zone rich in noncollagenous glycoproteins that stain nonspecifically with ruthenium red and chromic phosphotungstic acid (Yamamoto, 1986;Yamamoto and Wakita, 1990) and labels with 3H-mannose (Cho and Garant, 1989). These and other (Kurihara and Enlow, 1980a,b) authors have discussed the possibility that noncollagenous organic material accumulating at the DCJ and at remodeling alveolar bone surfaces may serve in matrix adhesion.…”
Section: Ultrastructural Distribution and Relationships Of Matrix Promentioning
confidence: 96%
“…Despite the presence of epidermal growth factor precursor in developing dental tissues (Snead et al, 1989), there is no evidence of its strong binding to differentiating cementoblasts (Cho et al, 19911, and it appears unlikely that this cytokine plays an important role in cementoblast differentiation. If in the initiation of cementogenesis, direct migration of cells toward root dentine is an obligatory step in early cementum synthesis, the signaling mechanism is transient; after cementum deposition, the cementoblasts detach and become part of the fibroblast population (Cho and Garant, 1989).…”
Section: Epithelial-hard Teeth Tissue Interactionsmentioning
confidence: 99%
“…Since fibronectin and the carboxyl terminal propeptides of procollagen contain mannose, the chemoattraction of precementoblasts may be attributed to the synthesis of these and other mannosecontaining matrix macromolecules. 9 Interestingly, Cho and Garant 9 found that after the onset of cementum deposition, the newly differentiated cementoblasts detach from the root surface and enter the fibroblastic compartment of the periodontal ligament.…”
Section: A Biologic Effects Of Matrix Molecules During Root Developmentmentioning
confidence: 99%